2000
DOI: 10.1177/002218560004200104
|View full text |Cite
|
Sign up to set email alerts
|

Major Tribunal Decisions in 1999

Abstract: Federal industrial relations in 1999 were marked by a continuing increase in the role played by the ordinary courts. This not only demonstrates the willingness of the parties to turn to the courts for assistance in resolving industrial disputes, but also reflects the increasing complexity and juridification of our industrial relations system. The diminished capacity of the Australian Industrial Relations Commission to arbi trate and the increased devolution of responsibility for industrial relations outcomes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The facts of the PP Consultants case have been examined in previous issues of this journal. 35 In short, a Full Court of the Federal Court overturned the initial decision of Matthews J by finding that an award which was previously applicable to St George Bank Ltd was binding on the operations of its 'bragent', PP Consultants Pty Ltd ('PP Consultants'). The Full Court, applying the 'substantial identity' test found that PP Consultants was a successor, assignee or transmittee of the business previously conducted by St George Bank at its Byron Bay branch.…”
Section: On 16 November 2000 the High Court Delivered Its Much Anticmentioning
confidence: 99%
“…The facts of the PP Consultants case have been examined in previous issues of this journal. 35 In short, a Full Court of the Federal Court overturned the initial decision of Matthews J by finding that an award which was previously applicable to St George Bank Ltd was binding on the operations of its 'bragent', PP Consultants Pty Ltd ('PP Consultants'). The Full Court, applying the 'substantial identity' test found that PP Consultants was a successor, assignee or transmittee of the business previously conducted by St George Bank at its Byron Bay branch.…”
Section: On 16 November 2000 the High Court Delivered Its Much Anticmentioning
confidence: 99%